POEZIA MODERNĂ DIN PERSPECTIVA ESTETICII RECEPTĂRII - Ursu, Cristina (CEP USM, 2020)
The current thesis tries to configure an alternative for interpreting modern poetry in terms of approximation of meaning. The relativism of interpretive reading is continually being expanded to a level approaching nihilism, thus compelling the need for creating new forms of interpretation. The aim of this paper is to discover significance in modern poetic texts by formulating analytical constructs that are flexible enough to admit a wide spectrum of interpretations.
Keywords: poezia modernă